Calculation of Corrective Signal for Adaptive Control Systems of Technological Processes of Oil Refining - Agayev, F.H.; Safarova, A.A. (Herald of Azerbaijan Engineering Academy, 2021)
The presented article considers the issue of calculation of corrective signals, which allows to carry out operative, parametric synthesis in order to provide the required quality parameters in the combined regulation system operating in the absence of information, taking into account the above conditions.